Electricity as a Factor of Competitiveness: Empirical Evidence in the Free Customer Market in the Context of Camisea Natural Gas - Peralta Neyra, Miguel Angel (2021)
The exploitation of Camisea natural gas implied benefits for industries with respect to the electricity rates of which they are large consumers. The national electricity market is based on three prices: busbar price, marginal cost, and free customer price. This study aims to establish whether the advantage of the low price of natural gas is reflected in the price for free customers, who are those who can directly negotiate their electricity tariff with the electricity generators or distributors. This was achieved through a time series analysis with econometric models linking the three national electricity market prices, which indicated the correlation between them. A review of the proposed models, their correlational analysis and the autocorrelation analysis of the residuals revealed a strong correlation between free market price and its first lag, which dissociates a correlation with the other prices; therefore, there is no real transfer of the gas price for a better tariff for the free costumer.